2010
DOI: 10.4102/sajcd.v57i1.46
|View full text |Cite
|
Sign up to set email alerts
|

Maximising health literacy and client recall of clinical information: An exploratory study of clients and speech-language pathologists

Abstract: Limited research has been carried out in the field of speech-language pathology with regard to ways of maximising health literacy and client recall. However, speech-language pathologists (SLPs) frequently provide vast amounts of information that clients need to understand, apply and review in order to manage their (or their child’s) health. This exploratory study aimed to contribute information about ways in which SLPs can overcome low health literacy and poor client recall so that treatment effectiveness is i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 23 publications
1
7
0
1
Order By: Relevance
“…Such findings corroborate the findings of other studies (8,26,32) . In fact, the majority of studies on validation of health literacy assessment instruments was composed of translations and adaptations of TOFHLA and REALM (22,26,37) .…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Such findings corroborate the findings of other studies (8,26,32) . In fact, the majority of studies on validation of health literacy assessment instruments was composed of translations and adaptations of TOFHLA and REALM (22,26,37) .…”
Section: Discussionsupporting
confidence: 83%
“…This professional's role is of utmost importance because of the close relation between health literacy and the skills of speaking, listening to and understanding oral/written language. Thus, it has been observed that patients with communication disorders clearly experience even greater challenges regarding health literacy (4,8,9) . In the current conjuncture, in which communication among the healthcare system, workers and users must be enhanced (7) , the Speech, Language and Hearing Scienceswhich are specially related to communication -can effectively contribute to improve speech, pragmatic language competences, and hearing, reading and writing skills (4,8,9) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…O número de publicações enfocando o tripé pretendido foi muito baixo. Dentre as 5 publicações identificadas (VON WUHLISCH;PASCOE, 2010;FAVORETTO et al, 2017), responderam plenamente à pergunta norteadora. As demais, foram aqui incluídas, porque de certa forma ajudam a identificar as lacunas referentes à abordagem deste tema, bem como apontam caminhos para estudos futuros.…”
Section: Discussionunclassified
“…In this context, the communicative and critical levels of the FHL must be considered for therapeutic efficacy. A case study carried out in South Africa, with a 43-year-old patient who presented with oropharyngeal dysphagia and low level of FHL, used high-tech strategies such as audio recordings in the form of CD/cassette, telephone contact, and text message, to maximize the FHL and the recovery of clinical information, with a greater understanding of the therapeutic process and greater motivation to perform the tasks involved in self-care for home rehabilitation (22) . Thus, the speech-language therapist must consider the individual's FHL to promote individualized strategies that guarantee the understanding and adherence to the procedures indicated in the rehabilitation of dysphagia.…”
Section: Discussionmentioning
confidence: 99%